A ciência do governar: positivismo, evolucionismo e natureza em Lauro Sodré - COELHO, Alan Watrin (Universidade Federal do Pará, 2013)
The journalistic polemic that, in 1881, involved the then lieutenant Lauro Sodré, bishop D. Macedo Costa and catholic newspaper A Boa Nova occurred in a moment in which the factors that provoked the future deterioration of the Brazilian Empire were already present in Brazilian society. In this work, we aimed at studying the confrontation as a discursive representation of an ideological clash in the social and intellectual aspects of Brazil in the late years of the XIX century: concerning Lauro Sodré, science and progress, appointed as fundamental instruments to the Republic; concerning A Boa Nova, faith and religion, considered essential instruments to the Monarchy. According to the philosophical-historical perspective of positivism, such questions were basic to the process of social evolution, including its political aspects. It shall be also noted that, in the masterpiece of evolutionist theory, Charles Darwin‟s On the origin of species by means of natural selection (1859), historical movement is decisively subordinated to natural laws and is, therefore, inserted in the broader process of evolution of the Universe. Evolution is effectively considered not as a simple movement, but as an improvement, a progress. To the positivist eyes of Lauro Sodré, the idea of a Monarchy connected to the survival of the conception of divine origin of Power appeared as a valid representation of the non-epistemological states of Humanity: the Metaphysical and the Theological ones; on the other hand, the Republic appeared as the only form of government “compatible with human dignity”. Projecting this polemic on the Brazilian mental realities of that time, we obtain, ultimately, the revelation of one of the components of the nature and forms that the complex relations between philosophical thought and hegemonic political object acquired in the movement of the ideas in Brazil towards the end of the XIX century.